(untitled) (Research, Society and Development, 2022)
Cattle farming is of paramount importance in agribusiness. It is known that reproduction represents an important link in the production chain and, thus, reproductive problems can cause great damage. Among the reproductive problems, pregnancy loss is one of the main reproductive problems that causes great productive damage, being characterized by embryonic death or premature expulsion of the fetus by bacterial, viral or parasitic agents. This review will describe the main characteristics (the agent, form of transmission, pathogenesis, clinical signs, diagnosis and control) of the diseases brucellosis, leptospirosis, bovine herpes virus type 1, bovine viral diarrhea, neosporosis and trypanosomosis responsible for triggering abortion in bovine females. Narrative literature review was used, with the arbitrary selection of works and use of bibliographic review for the interpretation and analysis of books, periodicals and reports from 2001 to 2021. It was observed the need to relate laboratory techniques for diagnosis, necropsy and signs clinics with the clinical history of the cow and property, in addition to the analysis of the fetus, fetal tissues and placenta. In addition, other reproductive problems related to low reproductive and productive efficiency were listed, such as infertility, heat repetition, death and embryonic resorption, mummification, stillbirth, birth of weak or neurologically impaired calves, placental retention, metritis and infections of the genital tract. It is concluded that knowledge about the characteristics of important bacterial, viral and parasitic diseases is important in obtaining the diagnosis, prevention and control of diseases in the herd, avoiding the loss of productivity and health of the animals.